EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM-BASED LEARNING (PBL) DAN OPEN-ENDED LEARNING (OEL) DENGAN PENDEKATAN SAINTIFIK PADA MATERI SEGI EMPAT DITINJAU DARI KREATIVITAS SISWA KELAS VII MTs NEGERI SE-KABUPATEN NGAWI TAHUN PELAJARAN 2014/2015 - Purwaningsih, Tri; Usodo, Budi; Sari Saputro, Dewi Retno (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract. The aims of this research are to know: 1) which learning models between OEL learning model using scientific approach, PBL scientific approach, or direct learning, give better achievement in learning quadrangle, 2) what kind of creativity between high creativity, medium creativity, or low creativity give better achievement, 3) in each studentsâ creativity, which learning model gives better achievement in mathematics learning between OEL using scientific approach, PBL using scientific approach, or direct learning, and 4) in each learning model, which one gives better achievement in mathematics learning or mathematics learning achievement between the students who have high creativity, medium, or low. This research was a quasi-experimental study by using a 3 x 3 factorial design. The population of the research was the seventh grades of MTsN in Ngawi regency in the Academic Year of 2014/2015. The sample was taken by using stratified cluster random sampling. Consist consisting of 318 students: 108 students in first experiment, 102 students in second experiment, and 108 students in control class. This experimental used independent variables that were learning model and the studentsâ creativity, and dependent variable was achievement in mathematics learning or mathematics learning achievement. Moreover, the validity test of instruments (the mathematics test and questionnaire) was done by validator. Then, the reliability of test instrument used KR-20 formula, whereas, the reliability of questionnaire used Cronbach Alpha. The internal consistency test of questionnaire was done by using Product Moment Correlation of Karl Pearson. The prerequisite test consists of Normality Test done by Lilliefors and Homogeneity Test using Bartlett. Then, data was analyzed by using two-way ANOVA.The results of the research are: 1) the mathematics learning using OEL with scientific approach gives better achievement than using PBL with scientific approach or direct learning, and PBL with scientific approach gives better achievement than direct learning, 2) the students who have high, medium and low creativity have same/equally mathematics learning achievement, 3) eachÂ creativity, the students who learn mathematics using OEL have better achievement than those who learnt mathematics using PBL and direct learning, while the students who learnt mathematics using PBL have better achievement than those who use direct learning, and 4) in each learning model, the students who have high, medium and low creativity have same/equally mathematics learning achievement.Keywords: Problem-Based Learning, Open-Ended Learning, Studentsâ Creativity.Â